2020
DOI: 10.1002/ece3.6277
|View full text |Cite
|
Sign up to set email alerts
|

A comparative plastomics approach reveals available molecular markers for the phylogeographic study of Dendrobium huoshanense, an endangered orchid with extremely small populations

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Hybridization, a driver of plant evolution, is common among terrestrial orchids [ 35 ]. Although dust-like seeds have the capacity to travel long distance [ 36 38 ], the results of this study showed that Bulbophyllum AN clade has diverged completely from SA clade in the late Oligocene (21.50–30.12 mya) [ 18 ]. Because the results of the JML software have ruled out the possibility of hybridization between the two clades [ 39 ], Bulbophyllum AN and SA clades have evolved independently for at least 25.81 million years.…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization, a driver of plant evolution, is common among terrestrial orchids [ 35 ]. Although dust-like seeds have the capacity to travel long distance [ 36 38 ], the results of this study showed that Bulbophyllum AN clade has diverged completely from SA clade in the late Oligocene (21.50–30.12 mya) [ 18 ]. Because the results of the JML software have ruled out the possibility of hybridization between the two clades [ 39 ], Bulbophyllum AN and SA clades have evolved independently for at least 25.81 million years.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, there are 39 species of Dendrobium with medicinal purposes, including D. huoshanense ( Chiang et al, 2012 ; Ye et al, 2021 ). However, the natural distribution of D. huoshanense is relatively narrow, because of its preference for a cool and moist environment, and high environmental requirements ( Liu et al, 2007 ; Qin et al, 2008 ; Niu et al, 2020 ). Wild D. huoshanense mainly grows as an epiphytic on the cliffs beside rivers and valleys at a slight altitude ranging between 200 and 1,200 m. In view of its strict requirements on the environment, D. huoshanense is currently endemic to the Da-bie Mountains, with Huoshan in the Anhui Province as the center of distribution ( Zha et al, 2007d ; Zheng et al, 2011 ; Wang et al, 2012 ; Wu et al, 2016 ).…”
Section: Resourcementioning
confidence: 99%
“…However, people over-excavate and conduct commercial trade for profit, thus causing serious damage to the wild resources [ 65 ]. This leads to a decline in the genetic differentiation among the Dendrobium species [ 66 ].…”
Section: Discussionmentioning
confidence: 99%